The Application of Posterior Plate in Tibial Plateau Fracture: A Case Report - Muhammad Zaim Chilmi; Firas Febrian (Journal Orthopaedi and Traumatology Surabaya)
Backgrounds: Tibial plateau fracture is the most frequent type of fracture caused by motor-vehicle collision. This injury may or may not be associated with soft tissue injury, such as the knee's ligaments. Posterior tibial plateau fractures are a rare subtype that requires surgical intervention. This case report describes the outcome of posterior plating in treating a posterior tibial plateau fracture.